A cloud computing-based damage prevention system for marine structures during berthing. (15th May 2019) - Jo, JunHo; Jo, ByungWan; Khan, Rana Muhammad Asad; Kim, JungHoon
Abstract: In this paper, a cloud computing-based damage prevention system for marine structures during berthing, consisting of a speed camera module and a cloud-computing based web server, is presented. The speed camera module consists of a laser distance sensor, a camera unit, and an LTE modem. These were installed on the marine structure to monitor the speed of ships during berthing. When the ship exceeds the berthing speed limit enacted by the Ministry of Oceans and Fisheries, an image of the ship and its speed data are transmitted to the web server via the LTE modem. This system was successfully tested at Maryang Harbor in Korea to confirm its feasibility. The web server activates an alert system when the image file is received, and the manager or other appropriate personnel can prevent or minimize damage from the berthing by responding immediately. All data were visualized and the berthing energy was calculated through the web server. Approved personnel can monitor the structure via the web server at any time and from anywhere. The system is effective in preventing and inspecting damages by berthing that can be used as an application of structural health monitoring for marine structures. Highlights: A damage prevention system for marine structure was developed to prevent or minimize damages during berthing. The system was able to monitor the berthing anytime anywhere with utilization of latest technologies. The system showed high suitability and can be used as an application of structural health monitoring for marine structures. This system was successfully tested in a harbor in Korea.